2019
DOI: 10.3389/fpsyg.2019.01353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupuncture on Chronic Stress-Induced Depression-Like Behavior and Its Central Neural Mechanism

Abstract: Depression is a serious psychiatric disorder with an enormous socioeconomic burden, and it is commonly comorbid with pain, chronic fatigue, or other inflammatory diseases. Recent studies have shown that acupuncture is an effective therapeutic method for reducing depressive symptoms; however, the underlying mechanism remains unknown. In this study, we investigated the effects of acupuncture on chronic stress-induced depression-like behavior and its central neural mechanisms in the brain. We induced chronic rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 65 publications
2
21
0
1
Order By: Relevance
“…Recent studies have provided laboratory-based evidence that acupuncture treatment can increase the expression of 5-HT1A receptors in the cortex, hippocampus, thalamus, and hypothalamus, as well as the expression of 5-HT1B in the cortex and thalamus. Therefore, acupuncture can effectively relieve depression symptoms [ 19 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have provided laboratory-based evidence that acupuncture treatment can increase the expression of 5-HT1A receptors in the cortex, hippocampus, thalamus, and hypothalamus, as well as the expression of 5-HT1B in the cortex and thalamus. Therefore, acupuncture can effectively relieve depression symptoms [ 19 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modern research has shown that acupuncture can stimulate the neuroendocrine of the body by stimulating specific points on the body. Therefore, acupuncture has a satisfactory therapeutic effect on diseases involving neuroendocrine pathological changes (such as chronic pain, menopause, depression, and insomnia) [ 19 , 20 ], with a very rare occurrence of adverse events.…”
Section: Introductionmentioning
confidence: 99%
“… 41 In addition, acupuncture could relieve depression-like behavior in the chronic restraint stress mice model by modulating the central brain neural activity and serotonin receptor. 42 Acupuncture relief for depressive disorders was proven by regulating the mTOR signal, neuropeptide Y, ERK-CREB pathway, glial glutamate transporter, and brain-derived neurotrophic factor. 42 Decreased serotonin and norepinephrine levels in the central nervous system, chronic inflammation, and increase of glutamate are related to the increased risk of developing depression in TN.…”
Section: Discussionmentioning
confidence: 99%
“…At PND39, the pups in the CRS and MS + CRS groups were subjected to CRS according to a previously reported protocol ( Campos et al, 2013 ; Lee et al, 2019 ). Briefly, the mice were placed in 50-mL conical tubes with air holes drilled into the sides to restrict their movements for 3 h (9:00–12:00 h) daily for 3 weeks.…”
Section: Methodsmentioning
confidence: 99%